State, Nationalism, and Islamization - Ali Saleem, Raja M. author. (orcid)0000-0002-1299-5944 Link aut Link
XIII, 303 p.
Keywords: This book argues that Islam’s role in state nationalism is the best predictor of the Islamization of government using two most different cases: Turkey, which was an aggressively secular country until recently, and Pakistan, a country that is synonymous with Islamization. It establishes a causal link between Islam’s role in state nationalism and Islamization of government during various periods of the history of both countries. The indicators used to establish the causal link between Islam’s role in state nationalism and Islamization are the presence of Islamic provisions in the constitution, Islam-inspired national symbols, Islamic images on the national currency, Islamic basis of family law, a Department of Religious Affairs, and governmental support for religious education. The book concludes by identifying three causal mechanisms—legitimacy, mobilization, and authenticity—that link Islam’s role in state nationalism and the Islamization of government.